Perception of Aesthetics in Contemporary Ceramic Art: The works of artist Dana Salahuddin al-Sharif as an example - Gzng Mohammed Abdulwahid; Sangar Qader Shekhmohammad Haji (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research entitled "Perception of Aesthetics in Contemporary Ceramic Art" ((The works of artist Dana Salahuddin al-Sharif as an example)) is an attempt to explain and demonstrate the aesthetic perception of the works of artist Dana Salah al-Din. Great attention has been given to the perception of the beauty of artistic and literary works. To be more familiar with and feel these concepts of the artworks of Kurdish artists. We are trying to answer several questions related to this topic, such as: Is it possible for a person to feel the beauty of artistic works through perception? Do contemporary ceramics artworks show a perception of beauty? There is no doubt that perception and beauty have a huge role in the development of artistic works, especially ceramic art. Through perception, some artists have been able to express their surroundings through their artworks, this motivated them to perform beautiful and great work in their artistic lives. The research is classified into four parts, the first part describes the general frame of the research and is devoted to, the first: the research problems, second: the research importance, third: the research objectives, fourth: research limits, fifth: research path, sixth. Definitions of the terms. The second part is devoted to the theoretical framework of the research, this research includes four axes, first: the theme of the relationship between perception and mind, second: the relationship between perception and beauty, third: the beauty between selfishness and objectivity. And the fourth: the characteristics of understanding aesthetic techniques in ceramic art. The third part of the research consists of: (Analysis of options), and the fourth part is about the results and sources. The third part of the study consists of: (Options Analysis), and the fourth part describes the results and sources.